Walisongo Road Walk Release Study - Dwi Wahyu Hidayat; Yuka Nur Wibisono (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2020)
The road is the national road Semarang Wali Sanga long 8.7 kilometers west of semarang, located at the entrance of the access from the West to the city of semarang. National road information previously never done pelebarannya before the year 2014. With this result on widening road capacity at his semarang information still high number of traffic congestion.Because of the way in a lot of information to go through buses and truck container that keeps the national road capacity road information become uncontrolled. road waliosngo semarang as the Centre of industry and shopping, side barriers many schoolgirls create a traffic jam on the road information semarang and creating road capacity information begins is not stable.Tujuhan of this research is to Examine the capacity of planning the widening of roads information in semarang city, previously done widening in 2014 with the results still the existence of road capacity which is not proportional to the volume path.